Altitude and hypoxic training in swimming - Truijens, M. J.; Rodriguez, F. A. (World Book of Swimming: From Science to Performance, 2011)
Altitude/hypoxic training is nowadays a common practice among swimmers although its benefits are still controversial in scientific literature. Traditional altitude training ("live high-train high") is still the most frequently used method in swimming, even though from a physiological perspective the "live high-train low" strategy appears to be a more promising alternative. While acute hypoxia deteriorates swimming performance, chronic hypoxia may induce acclimatization effects, mainly through the acceleration of red blood cell production, which could improve aerobic capacity and therewith performance upon return to sea level. Other potential benefits such as improved exercise economy, enhanced muscle buffer capacity and pH regulation, and improved mitochondrial function have also been postulated. In order to get a better picture of the potential usefulness of altitude and hypoxic training in swimming this chapter will (i) briefly review the acute and chronic effects of hypoxia, (ii) describe traditional and current methods of altitude/hypoxic training, (iii) discuss the scientific evidence on the effects of altitude/hypoxic training on sea level swimming performance, and (iv) give some practical guidelines for altitude/hypoxic training.